Adsorption characteristics of clay minerals in shale. (17th January 2018) - Gu, Yang; Ding, Wenlong; Yin, Shuai; Yin, Min; Xiao, Zikang
ABSTRACT: Based on the adsorption potential theory, this paper describes the adsorption characteristics of four kinds of clay minerals, i.e. Montmorillonite, Kaolinite, Chlorite, and Illite, in clay shales, meanwhile adding quartzite as control sample. We focus on adsorption amount a, differential adsorption work A, characteristic energy E, characteristic coefficient n in adsorption potential analysis. The results show that the differential adsorption work decreases as the adsorption energy increases, which can generally represent the change features during each stage; the optimum value of n is around 1.5 for five kinds of inorganic minerals; E slightly decreases as the temperature increases. For clay minerals, the absolute values of adsorption heat and the result of maximum adsorption can meet that Montmorillonite> Kaolinite> Chlorite> Illite.